Ways to Improve the Efficiency of the Seed Hair Removal Machine with the Improvement of its Construction (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, recommendations are given on the use of modified saw cylinders instead of metal brush drums used in seed dehairing machines, and it is possible to obtain 2.5-3.0% type "B" fluff from seeds with a hairiness of 9.0% when using saw cylinders.